2014
DOI: 10.1111/1556-4029.12541
|View full text |Cite
|
Sign up to set email alerts
|

Underrepresentation of Heroin Involvement in Unintentional Drug Overdose Deaths in Allegheny County, PA

Abstract: Drugs contributing to overdose deaths are listed on death certificates, but their validity is rarely studied. To assess the accuracy of "morphine" and "codeine" listings on death certificates for unintentional overdose deaths in Allegheny County, PA, investigative and laboratory reports were reviewed. Deaths were reclassified as heroin-related if documentation showed 6-monoacetylmorphine in blood or urine, "stamp bags" or drug paraphernalia at scene, history of heroin use, or track marks. Deaths were considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 12 publications
1
26
0
1
Order By: Relevance
“…Second, drug mentions on death certificates may contain errors. For instance, heroin use may sometimes be attributed to morphine or codeine . Third, some ICD‐10 codes lack desired specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Second, drug mentions on death certificates may contain errors. For instance, heroin use may sometimes be attributed to morphine or codeine . Third, some ICD‐10 codes lack desired specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Only the presence of 6-acetylmorphine can confirm heroin use; therefore, heroin-involved cases might be undercounted (9). Sensitivity analyses was performed by reclassifying these cases as heroin-involved, but the findings did not change.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in the attribution of heroin‐related deaths has been demonstrated to contribute to the under‐reporting of these cases. The re‐examination of unintentional drug overdose deaths in the United States led to the identification of a large number of heroin‐related deaths that had been attributed to morphine and codeine toxicity, as well as cases that were missed because of inconsistencies in the cause of death certification . Previous studies have demonstrated a reliance on 6‐AM detection, the generally limited use of alternate toxicological markers such as morphine and codeine ratios as evidence of heroin use which can contribute to variability in the attribution of a death to heroin .…”
Section: Discussionmentioning
confidence: 99%
“…Heroin‐related death investigation can be particularly challenging; because of variability in the detection of heroin‐specific metabolites, toxicological analysis may not be feasible at all, and most cases are complicated by multiple substance use . The challenges associated with the interpretation of toxicity data in heroin‐related death cases have also resulted in the misclassification of heroin‐related deaths as being morphine‐related when heroin‐specific toxicological markers such as 6‐acetylmorphine (6‐AM) are not detected, which further contributes to the under‐reporting of these deaths .…”
Section: Introductionmentioning
confidence: 99%